Ezra Pound and the career of modern criticism professional attention - Coyle, Michael 1957-; Preda, Roxana 1959- (Studies in American literature and culture. Literary criticism in perspective, 2018)
This first book-length study of Pound criticism investigates not just what critics have had to say about Pound but also why they have asked the questions they have asked